Pengembangan Model PBM IPA Berorientasi PKP Untuk Meningkatkan Daya Nalar Siswa - Mohamad Nur; Muchlis S.; Juliani Djajadi; M. Cholik; Ismet B.; Munoto Munoto; Sumiarsih Sumiarsih; Made Muliatna; Marsudi Marsudi; T. Wrahatnolo; M. Ibrahim; Ali Mufie Arief (Universitas Negeri Malang, 2016)
This study is a follow up the first one in which it was revealed that the student's process skill could be improved significantly within a relatively short time. In the first study the package developers or the researches themselves were the managers of the teaching learning process for the entire packages. The purpose of this second study was to find out whether those learning packages were still effective if the managers of the teaching-learning process were the teachers.